Innovation Theory in Advanced Teaching Technology - Mallillin, Leovigildo Lito (LPPM STKIP Kusuma Negara, 2025)
The study aims to examine the innovation theory in advanced teaching technology trends in the educational system on innovative teaching methods, improve collaborative teaching, teaching and learning process. This includes the trends in making innovation of teaching technology theory in the educational system among the respondents. The research utilized the quantitative research design because it aims to discover the sample size of the population of the study on quantified responses and concentration on the format standard of quantitative research design to ensure the concrete analysis of the data. Stratified quota sampling is employed in the study. It is the most common method of sampling nonprobability. The study comprised One hundred Five (175) respondents only. Results show innovative teaching processes in new teaching trends in strategy proactive classroom methods and techniques, show to enhance and focus on critical thinking and problem-solving skills in categorizing the planning in multiple perspectives of learning, and show to monitor the improved planning of student’s evaluation to promote deeper thinking and knowledge of teaching and learning process. Findings show that there is a significant correlation on the trend of teaching technology innovation theory in the educational system as observed by the respondents.